2019
DOI: 10.1055/s-0039-3402687
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Platelets in Premature Neonates with Intraventricular Hemorrhage: A Systematic Review and Meta-Analysis

Abstract: Intraventricular hemorrhage (IVH) affects up to 22% of extremely low birth weight neonates. Impaired coagulation might contribute to the pathogenesis of IVH. The aims of this study were to summarize the current knowledge on the role of platelet indices in premature neonates with IVH and to provide an overview of secondary hemostasis parameters as well as fibrinolysis in premature neonates with IVH. The review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 48 publications
(349 reference statements)
3
8
0
Order By: Relevance
“…Hemorrhage in preterm neonates is often observed in parallel with thrombocytopenia, without any apparent causality between platelet count and bleeding risk [ 73 ]. Thrombocytopenia does not stand alone as a risk factor for bleeding events, and thus there is a need to develop laboratory tests to provide a better correlation with bleeding risk other than platelet count alone, especially tests that focus mainly on platelet function.…”
Section: Platelet Function Assessmentmentioning
confidence: 99%
“…Hemorrhage in preterm neonates is often observed in parallel with thrombocytopenia, without any apparent causality between platelet count and bleeding risk [ 73 ]. Thrombocytopenia does not stand alone as a risk factor for bleeding events, and thus there is a need to develop laboratory tests to provide a better correlation with bleeding risk other than platelet count alone, especially tests that focus mainly on platelet function.…”
Section: Platelet Function Assessmentmentioning
confidence: 99%
“…The etiology of IVH is incompletely understood, but it is believed to be multifactorial 8–11 . Thrombocytopenia affects up to 70% of preterm neonates with birthweight <1000 g, 12 and studies have found that IVH is often co‐observed with thrombocytopenia 13,14 . Nevertheless, platelet count alone appears to be a poor predictor for IVH 14–17 .…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 , 10 , 11 Thrombocytopenia affects up to 70% of preterm neonates with birthweight <1000 g, 12 and studies have found that IVH is often co‐observed with thrombocytopenia. 13 , 14 Nevertheless, platelet count alone appears to be a poor predictor for IVH. 14 , 15 , 16 , 17 Interestingly, it has been suggested that once the bleeding has occurred, a reduced platelet function in the preterm might contribute to expansion of the bleed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Grevsen et al present a systematic review and meta-analysis of the role of platelet counts and other platelet indices in premature neonates with intraventricular hemorrhage. 16 Moreover, current knowledge on the impact of secondary hemostasis and fibrinolysis is highlighted. One major finding presented by the authors is that neonates with platelet counts <100 Â 10 9 /L during the first week of life have an increased incidence of intraventricular hemorrhage.…”
mentioning
confidence: 99%